A Self‐Powered High‐Performance UV Photodetector Based on Core–Shell GaN/MoO3–x Nanorod Array Heterojunction. Issue 15 (13th May 2020) - Zheng, Yulin; Li, Yuan; Tang, Xin; Wang, Wenliang; Li, Guoqiang
Abstract: Self‐powered UV photodetectors are highly desirable for applications in space communications and environmental monitoring. However, most self‐powered UV photodetectors exhibit unimpressive performance in weak signal detection. Herein, a self‐powered UV photodetector based on the core–shell GaN/MoO3– x nanorod array (NRA) heterojunction system is demonstrated. Homogeneous MoO3– x layers are deposited on GaN NRAs by a simple one‐step physical vapor deposition method. The photodetector device shows an ultrahigh specific detectivity of 2.7 × 10 15 Jones at 355 nm without any power supply. Further analyses reveal a responsivity of 160 A W −1 and a high UV–vis rejection ratio ( R 355 nm / R 400 nm ) of 2.0 × 10 4 under zero bias. The self‐powered device also has a fast response speed with a rise/fall time of 73/90 µs. As a result, the self‐powered photodetector, featuring ultrahigh detectivity and responsivity along with fast response, exhibits great potential for applications in next‐generation UV detection. The core–shell NRA structure heterojunction design provides a valuable direction for realizing nanoscale self‐powered UV photodetectors. Abstract : A hybrid core–shell heterostructure system that consists of GaN nanorod array cores and MoO3– x shells is synthesized and a self‐powered UV photodetector based on core–shell GaN/MoO3– x heterostructure is demonstrated. The device exhibits detectivity as high as 2.7 × 10 15 Jones at 355 nm without any power supply.